Y/x=k
when y=9, then x= -3
9/-3=-3
⇒ k= -3
Answer:
(3, 2), (2, 3)
Step-by-step explanation:
x + y = 5
xy = 6
Solve the first equation for x.
x = 5 - y
Substitute 5 - y for x in the second equation.
xy = 6
(5 - y)y = 6
5y - y² = 6
y² - 5y + 6 = 0
Factor.
(y - 2)(y - 3) = 0
y - 2 = 0 or y - 3 = 0
y = 2 or y = 3
Now substitute 2 for y in the first equation and solve for x.
x + y = 5
x + 2 = 5
x = 3
One solution is x = 3; y = 2, or (3, 2).
Now substitute 3 for y in the first equation and solve for x.
x + y = 5
x + 3 = 5
x = 2
Another solution is x = 2; y = 3, or (3, 2).
Answer: (3, 2), (2, 3)
The answer would be J because if the equation was transferred into a positive then it would be 2y and 5x marking 5x on the bottom and 2y vertically.
Hope this helps!!
Blue 9 x 3 = 27
red 3 x 3 = 9
27 + 9 = 36
I hope this helps
Coordinates for new triangle -
P’(-1,1)
Q’(-3,3)
R’(-3,1)